1978
DOI: 10.1073/pnas.75.1.270
|View full text |Cite|
|
Sign up to set email alerts
|

Electron microscopic determination of the binding sites of ribosomal proteins S4 and S8 on 16S RNA.

Abstract: Specific complexes.early in the assembly of Escherichia coil ribosomes were examined in the electron microscope. Complexes between ribosomal protein S4 or S8 and 16S RNA were fixed gently with formaldehyde and then denatured for protein-free spreading. Binding of each protein was found to preserve an easily recognized configuration in the RNA that allows the sites of protein binding to be determined. S8-16S RNA complexes have a single hairpin loop near the middle of the 16S RNA, 798 + 21 bases from one end and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Analogously, the regA protein could recognize a site of six nucleotides or so. A site of this size is compatible with the D (53)(54)(55)(56). However, given the genetics (Fig.…”
supporting
confidence: 54%
“…Analogously, the regA protein could recognize a site of six nucleotides or so. A site of this size is compatible with the D (53)(54)(55)(56). However, given the genetics (Fig.…”
supporting
confidence: 54%
“…First, it is likely that protein S4 occupies some central position in the 30S particle: (i) it is distinguished by the most reported crosslinks and interactions with other proteins (4, 6, 10, 28); (ii) it has no antigenic determinants on the surface of the particle and thus is buried inside (30); (iii) it is bound simultaneously with several extended but noncontiguous regions of the 16S RNA chain (28,31,32). The central position and the unique binding of globular protein S4 to remote long sections of the RNA chain could be realized in the most natural way if it was positioned between the two branches of the Y-shaped RNA molecule, interacting with both the branches.…”
mentioning
confidence: 99%
“…These regions with large variation are often characterized by a high incidence of imperfect base pairs (U-G and A-G) in the helices. It has been shown that many of these irregular helices bind ribosomal proteins; for example, ribosomal protein S8 binds to the region 588 to 652 (Cole et al, 1978;Olins and Nomura, 1981). It has been proposed that the binding of protein stabilizes the helix and thereby allows more nonpairing or formation of weak base pairs (Noller and Woese, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This region is the binding site for protein S8 in E. coli and in archaebacteria (Cole et al, 1978;Olins and Nomura, 1981). This region also accounts for the large increase in size of the 18S rRNA of eukaryotes (Zweib et al, 1981).…”
Section: Region 588 To 651mentioning
confidence: 97%